1991
DOI: 10.1271/bbb1961.55.1417
|View full text |Cite
|
Sign up to set email alerts
|

Leaf surface glycolipids from Nicotiana acuminata and Nicotiana pauciflora.

Abstract: Glycolipids containing short-chain fatty acids are important tobacco smokearoma precursors, especially in oriental tobacco.*~3) They are contained in the surface lipids of tobacco plants. Previously, we have classified Nicotiana species tentatively by the nature of the surface glycolipids into 1) N. species having no glycolipids, 2) N. species having mainly glucose esters, 3) N. species having mainly sucrose esters, and 4) N. species having both glucose esters and sucrose esters.4) In this classification, N.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 2 publications
1
19
0
Order By: Relevance
“…Sucrose esters isolated from cuticular extracts of other Nicotiana species have been suggested to possess only two C 3 to C 8 acyl moieties and may have from one to four acetyl groups on the fructose. In summary, about 19 different structural types (Figure 1) of sucrose esters have been reported for Nicotiana species, and for any sugar type, a series of homologs are found due to differing acyl groups (7)(8)(9)(10)(11)(12)(13)(14). Sucrose esters regardless of their structure present real challenges in terms of isolation, sample preparation, and molecular characterization because the materials are partially esterified with linear and branched fatty acids of variable chain length.…”
Section: Introductionmentioning
confidence: 99%
“…Sucrose esters isolated from cuticular extracts of other Nicotiana species have been suggested to possess only two C 3 to C 8 acyl moieties and may have from one to four acetyl groups on the fructose. In summary, about 19 different structural types (Figure 1) of sucrose esters have been reported for Nicotiana species, and for any sugar type, a series of homologs are found due to differing acyl groups (7)(8)(9)(10)(11)(12)(13)(14). Sucrose esters regardless of their structure present real challenges in terms of isolation, sample preparation, and molecular characterization because the materials are partially esterified with linear and branched fatty acids of variable chain length.…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analysis of acylsugar-producing species point to sucrose as the ASAT ancestral acyl acceptor – it is the sugar acceptor in earlier diverging lineages leading to S. sinuata and P. axillaris (Moghe et al, 2017; Nadakuduti et al, 2017). Further, acylsucrose-accumulating species are present throughout the Solanaceae family (Burke et al, 1987; King and Calhoun, 1988; Matsuzaki et al, 1991; Maldonado et al, 2006; Ghosh et al, 2014; Liu et al, 2017; Moghe et al, 2017), whereas reported acylinositol accumulators are S. quitoense and S. lanceolatum ( Fig. 1 ) (Herrera-Salgado et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…[28,29] , and cheese and milk fat [30]. This compound is contained in fruits as one of bound aroma compounds [31,32] or one of lipid constituents [33,34]. Moreover, the substance is known as nutritional requirement of some microorganisms [35] or as protective compound in some insect [36].…”
Section: Methodsmentioning
confidence: 99%